Renewable Energy Potential From Micro Hydro For Techno-Economic Uplift – A Brief Review - Min, Tian Chuan; Mohammad Iskandar, Jobli; Abu Saleh, Ahmed; Robert, Malong; Masri, Zaini; Mohammad Omar, Abdullah; Mohd Narzam, Jaffar; Mohamad Abdullah, Ali (International journal of recent research and applied studies, 2011)
Modern world requires energy more than ever. As the global population and modernization exhibit seemingly ever upward trends, it is certain that the crave for energy will continue to rise. However, conventional energy is depleting at an alarming pace, though renewable energy seems to prospect a promising alternative. Being one of the more established and successful renewable energy technologies, the authors attempt to review the micro hydro as well as its potential in providing sustainable energy to the mankind.